Réponses

2013-09-29T20:30:33+02:00
Pour le 1 et le 2 je trouve la meme solution
3)   \frac{2}{9} - \frac{21}{36} = \frac{8}{36} - \frac{21}{36} = -\frac{13}{36}
4)  -1+8 *  \frac{7}{9} = -1+ \frac{56}{9} = \frac{47}{9}
5)  \frac{-18-10}{15} * \frac{1}{5} = \frac{-28}{15} * \frac{1}{5} = -\frac{28}{75}
6)  \frac{3}{4} * \frac{-9}{8} + \frac{5}{6} = \frac{-27}{32} + \frac{5}{6} = \frac{-162+160}{192} = -\frac{1}{96}
7)(\frac{11}{7} - \frac{35}{7}) * \frac{21}{2} = \frac{-24}{7} * \frac{21}{2} =-36
8)
8) (3/7*1/15)-8=1/35-8=-279/35
Merci beaucoup